The threat of artemisinin resistant malaria in Southeast Asia. - Hanboonkunupakarn, B; White, N (Elsevier, 2016)
Fifty years ago it was becoming clear that the enormous global effort to eradicate malaria had failed. There were also an increasing number of worrying reports that the wonder drug chloroquine was not working as it should against falciparum malaria in parts of South-East Asia and South America. Chloroquine resistance spread slowly at first, but by 1979 it had reached the Eastern coastline of Africa, and by 1992 it had crossed the entire continent. Chloroquine could no longer be relied upon to treat malaria, and its preventive efficacy was also in decline. Chloroquine was replaced eventually by sulfadoxine-pyrimethamine as first-line treatment, but this fell rapidly to resistance in many places. Later it was shown by analysis of the sequences flanking the mutant resistance genes (Pfcrt and Pfdhfr respectively) that the parasites causing illness and death in Africa had their genetic origins close to the Thailand-Cambodia border [1, 2]. In 1984 mefloquine was introduced as first-line treatment for falciparum malaria in Thailand, but resistance soon followed. The prospect of truly untreatable malaria loomed. The region was saved qinghaosu (artemisinin), a Chinese traditional remedy that has since become the cornerstone of recommended antimalarial treatments [3]. In the treatment of severe malaria parenteral artesunate was shown to reduce mortality substantially and so has become the treatment of choice. Artemisinin-combination therapies (ACTs) are now the first-line treatment for uncomplicated P. falciparum malaria throughout the tropical world, and they are increasingly recommended for vivax malaria [3]. But the history of antimalarial resistance emergence and spread is beginning to repeat itself.